Penguatan Pendidikan Karakter Remaja Masjid melalui Kegiatan Workshop di Masjid Kampus Al-Furqon UPDN Nganjuk - Muhamad Ali Anwar; Nur Fuad; Agus Tohawi; Anik Indramawan; Leily Vidya Rahma; Mastur Mastur; Linda Apriliani (Eastasouth Journal of Effective Community Services, 2022)
This workshop was conducted to reinforce character education among the youth of the Al-Furqon Campus Mosque, UPDN Nganjuk, through the integration of religious and moral principles into everyday routines. The activities applied participatory approaches, including worship practice sessions, group discussions, and interactive lectures, to cultivate core traits such as discipline, responsibility, integrity, self-confidence, and empathy. The planning and management of mosque-based programs, including congregational prayer, Quran recitation, and religious talks, proved effective in embedding these values. Assessment using observation and participant feedback showed meaningful improvement in character growth and involvement among participants. The program also underlined how supportive leadership and practical, context-relevant activities help maintain consistent youth participation. Overall, the results indicate that character education centered in mosque activities can significantly contribute to strengthening adolescents’ moral and spiritual foundations.